STRATEGI PROMOSI PRIORITY BANKING OFFICER PADA BANK TABUNGAN NEGARA KANTOR CABANG DEPOK. - Endah Agustina Muziarti (2023)
commercial bank is a bank that conducts banking activities such as payment transactions based on established procedures and rules. In this case, conventional banks are banks that engage in extensive commercial activities. Bank Tabungan Negara (BTN) is one of the government-owned banks in Indonesia. It was established in 1897 and is the first savings bank in Indonesia. Priority Banking is an exclusive banking service offered to customers who have high net worth or meet specific criteria set by the bank. A Priority Banking Officer (PBO) is an employee who serves as a personal banker, financial advisor, and marketing officer for providing products to Priority Banking customers. This service provides access to superior banking products and services, as well as personalized and guaranteed service. Promotion is a crucial activity that actively plays a role in introducing, informing, and reminding consumers about the benefits of a product to encourage them to make a purchase. The promotion strategy used by Priority Banking Officers is direct marketing promotion strategy that utilizes Below The Line media, including various media such as direct gifts, gatherings, flyer programs, marketing kits, and they have special strategies to attract their customers, such as the Customer Is Our Family approach, data upgrades, referrals, and priority gatherings.